Low concentration of Bisphenol a induces proliferation of gastric cancer cells, HGC-27 - Hanafi, Noorul Izzati (Penerbit UTM Press, 2019)
Bisphenol A, an endocrine disrupting compound that affects human homeostasis. Studies on BPA are focusing on the impact of BPA in reproductive function and brain development. However, the effect of BPA on gut especially gastric cells is not well explored. Gut is directly in contact with ingested BPA; therefore, we aimed to determine the effect of BPA exposure on gastric cells proliferation at safe recommended concentration. Human gastric cancer cells (HGC-27) were treated with BPA at different concentration (low: 10-9M, 10-7M; high10-5M, 10-4M) and time point (24 hr, 48 hr, 72 hr). Cell viability assays were determined using MTS assay. Cells were further stained with Alexa Fluor-635 (F-actin) and Fluorescein (Hif-1α) protein for immunocytofluorescence. Data were analysed using ANOVA (p<0.05, n≥3). Cells treated with 10-9M BPA showed significance increase of cell viability after 48 hr (Mean ±SEM; 146%±0.03, p=0.01) and 72 hr (113%±0.03, p=0.00) compared to 24 hr treatment (77%±0.11, p=0.002). Similarly, cell treated with 10-7M BPA showed a significance increase after 48 hr (141%±0.03, p=0.03) and 72 hr (190%±0.03, p=0.02) compared to 24 hr cells treated with 10-7M (88%±0.05, p=0.01) and untreated (100%±0.07). Lower concentration of BPA increases the condensation of F-actin in all HGC-27 cells. Meanwhile, translocation of Hif-1α protein were observed in all BPA-exposed cells. Findings of this study revealed that BPA induced proliferation and condensation of F-actin structure of gastric cancer cells at low concentration.